The peculiar pumpkin thief - STILTON, GERONIMO (b)
In The Peculiar Pumpkin Thief (Geronimo Stilton #42), all pumpkins vanish from New Mouse City just days before Halloween, threatening the holiday. Geronimo Stilton teams up with detective Hercule Poirat to investigate the thefts, which coincide with a mysterious new theme park, leading to a race against time to save Halloween.
English